Effect of hydroxypropyl-ß-cyclodextrin complexation on the aqueous solubility and stability of artesunate - Sunderland, Bruce (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objectives: The effect of inclusion complexes of artesunate (ART) with hydroxypropyl-ß-cyclodextrin (HP-ß-CD) at selected pH values on the phase solubility profile and stability of ART in aqueous solution was investigated. Methods: Phase solubility studies were performed in 0.20 M phosphate buffer solutions and 0.5 μ of pH values 3.00, 4.00, 5.00 and 6.00. ART (1 g) was added for all samples of 0, 52, 104 and 156 m mole of HP-ß-CD and agitated at 100 rpm and 25 °C ± 0.6 °C in an orbital shaker until equilibrium was achieved. Results: The phase solubility profile of the complex was classified as AL-type, indicating the formation of a 1:1 stoichiometric inclusion complex. A complex of ART with HP-ß-CD (272 mg mL-1) showed a 25-fold increase in solubility compared to ART at pH 3.0. The stability constants (Kst) of the inclusion complexes were 83, 73 and 60 mole-1. Conclusion: Solubility and stability of ART in aqueous solution was increased in the presence of HP-β-CD. at pH 6.0, 7.0 and 8.0 respectively. The activation energies (Ea) were obtained from Arrhenius plots of degradation rate constants in the presence and absence of HP-ß-CD. The thermodynamic parameters of activation enthalpy and entropy were obtained from Eyring Equation. The activation energies Ea in the absence and presence of HP-ß-CD were 93.4 and 95.8 kJ/mole respectively. The shelf-life of ART in the presence of HP-ß-CD was increased more than 4-fold.